Jane Austen and Performance - Cano, Marina. author. aut Link
XIV, 212 p. 14 illus.
Keywords: This is the first exploration of the performative and theatrical force of Austen’s work and its afterlife, from the nineteenth century to the present. It unearths new and little-known Austen materials: from suffragette novels and pageants to school and amateur theatricals, passing through mid-twentieth-century representations in Scotland and America. The book concludes with an examination of Austen fandom based on an online survey conducted by the author, which elicited over 300 responses from fans across the globe. Through the lens of performative theory, this volume explores how Austen, her work and its afterlives, have aided the formation of collective and personal identity; how they have helped bring people together across the generations; and how they have had key psychological, pedagogical and therapeutic functions for an ever growing audience. Ultimately, this book explains why Austen remains the most beloved author in English Literature.